Globus pallidal deep brain stimulation for Tourette syndrome: Effects on cognitive function. (December 2019) - Cappon, Davide; Beigi, Mazda; Kefalopoulou, Zinovia; Zrinzo, Ludvic; Candelario, Joseph; Milabo, Catherine; Akram, Harith; Dayal, Viswas; Hyam, Jonathan; Kass-Iliyya, Lewis; Silverdale, Monty; Evans, Julian; et al.
Abstract: Introduction: In a double-blind randomized crossover trial, we previously established that bilateral deep brain stimulation of the anteromedial globus pallidus internus (GPiam-DBS) is effective in significantly reducing tic severity in patients with refractory Tourette syndrome (TS). Here, we report the effects of bilateral GPiam-DBS on cognitive function in 11 of the 13 patients who had participated in our double-blind cross-over trial of GPi-DBS. Methods: Patients were assessed at baseline (4 weeks prior to surgery) and at the end of each of the three-month blinded periods, with stimulation either ON or OFF. The patients were evaluated on tests of memory (California Verbal Learning Test-II (CVLT-II); Corsi blocks; Short Recognition Memory for Faces), executive function (D-KEFS Stroop color-word interference, verbal fluency, Trail-making test, Hayling Sentence Completion test), and attention (Paced Auditory Serial Addition Test, Numbers and Letters Test). Results: GPiam-DBS did not produce any significant change in global cognition. Relative to pre-operative baseline assessment verbal episodic memory on the CVLT-II and set-shifting on the Trail-making Test were improved with DBS OFF. Performance on the cognitive tests were not different with DBS ON versus DBS OFF. GPiam-DBS did not alter aspects of cognition that are impaired in TS such as inhibition on the Stroop interference task or the Hayling Sentence Completion test. Conclusions: This study extends previous findings providing data showing that GPiam-DBS does not adversely affect cognitive domains such as memory, executive function, verbal fluency, attention, psychomotor speed, and information processing. These results indicate that GPiam-DBS does not produce any cognitive deficits in TS. Highlights: We assessed the impact of bilateral deep brain stimulation of the anteromedial globus pallidus internus (GPiam-DBS) on cognitive functions. Neuropsychological battery was designed to measure memory, executive function, verbal fluency, psychomotor speed and attention. We demonstrate no improvement in any cognitive processes that are usually impaired in Tourette patients following GPiam-DBS. We found no significant changes in memory, executive functions and attention following GPiam-DBS surgery.. We provide evidence of cognitive safety of GPiam-DBS surgery in TS